Peanut exposure during pregnancy, breastfeeding and complementary feeding: perceptions of practices in four countries. (16th November 2014) - Boulay, Annabelle; Gancheva, Vyara; Houghton, Julie; Strada, Anna; Sora, Beatriz; Sala, Roser; Rowe, Gene
Abstract Food allergy is an increasing problem worldwide. Allergy to peanuts is a particular concern, given that this is rarely outgrown and may be associated with life‐threatening anaphylaxis. However, it is unclear what factors are responsible for a perceived increase in prevalence rates. One matter on which scientists agree, however, is that exposure to peanuts early in life is significant – although whether early exposure protects or sensitizes to allergy is unclear. There is no significant research that currently records differences in early life exposure either within or between populations. This exploratory study makes a first step in this direction using focus groups conducted in four countries with disparate 'peanut experiences' to characterize early exposure in these. The ultimate aim is to help in the development of a survey instrument to attain nationally representative samples of consumers and hence to use the results from this to compare with allergy prevalence data collected in other parts of the European Union‐funded 'EuroPrevall' project. The results in this study not only reveal considerable similarities across countries (e.g. in terms of lack of knowledge of guidelines; lack of changes in feeding behaviour during/after pregnancy, feelings that diet variety in children is important) but also one or two interesting and potentially important differences, such as increased consumption in Bulgarian (and some Spanish) breastfeeding mothers because of the ability of peanuts to facilitate lactation. Study limitations and future study intentions are also discussed.